IMPLICATIONS OF URBANIZATION ON HOUSING CONDITION IN GWAGWALADA TOWN, ABUJA, NIGERIA. - Ahmed Belel, Waheeda; Ahmed Belel, Zaheeda; Belel Ahmad, Zaynab; Abubakar, Mahmoud Hijab (Journal of Technology Management and Business, 2019)
There is massive movement from the rural to urban areas; leading to shortages in housing and social amenities. This paper, therefore, examines the implications of urbanization on housing condition in Gwagwalada town. The objectives of the study are to find out the factors that lead to urbanization, the housing conditions in the study and the effects of rapid population growth on housing condition. Descriptive statistics and ranking method were employed to resolve these objectives. Questionnaires were distributed in three wards of the study area. A sample size of 100 responded was selected using the Taro Yamane’s formula. The research findings show that upsurge population growth is caused by migration; the population growth affects the quality, quantity and environmental facilities of housing. The research recommended that if urbanization is properly managed, will bring about economic and social development. Also planning backed by reliable data should be embarked in order to tackle the growth in formal settlements.